Analysis on Human Adaptive Levels in Different Kinds of Indoor Thermal Environment. (2015) - Song, Xiaoji; Yang, Liu; Zheng, Wuxing; Ren, Yimei; Lin, Yufan
Abstract: To reveal the law of human adaptive level changing along with indoor temperature and humidity in naturally ventilated buildings, an approach of field survey of thermal comfort has been carried out in an university of Guangzhou for about a year, and adaptive coefficient (λ) proposed in adaptive PMV model (aPMV) has been used to calculate the level of adaptation in different combination of indoor temperature and humidity. The results show that, the effects of different combinations of indoor temperature and humidity on human adaptive level vary from each other obviously, the level of adaptation in cool and dry environment (CDE) and comfortable environment (CE, PMV<0) was low, but it is high in hot and humid environment (HHE) and CE (PMV>0) .The adaptive coefficient (λ) are 0.64 (HHE), -0.06(CE, PMV<0), 1.07(CE, PMV>0) and -0.37 (CHE), respectively.